EU harmonization, managerial perceptions and SME export behavior - Yamin, Mo; Sinkovics, Rudolf R.; Hadjielias, Elias (My University, 2007)
This paper examines the impact of EU harmonization on promoting exports by SMEs. The paper develops hypotheses on the positive impact of EU harmonization in enhancing stimuli and reducing barriers to exporting beyond the immediate or direct effect of harmonization. The empirical focus of the paper is on the food & beverage sector in Cyprus, employing paired-sample t-test comparing SME perceptions 'before' and 'after' in relation to harmonization. The study shows that compliance contributes towards an overall increase in management perceptions of export stimuli, and an overall reduction in management perceptions of export barriers.
Keywords: European Union; Export barriers; Export promotion; Harmonization